Fibroblasts derived from long‐lived insulin receptor substrate 1 null mice are not resistant to multiple forms of stress. Issue 5 (24th July 2014) - Page, Melissa M.; Sinclair, Amy; Robb, Ellen L.; Stuart, Jeffrey A.; Withers, Dominic J.; Selman, Colin
Summary Reduced signalling through the insulin/insulin‐like growth factor‐1 signalling (IIS) pathway is a highly conserved lifespan determinant in model organisms. The precise mechanism underlying the effects of the IIS on lifespan and health is currently unclear, although cellular stress resistance may be important. We have previously demonstrated that mice globally lacking insulin receptor substrate 1 (Irs1−/−) are long‐lived and enjoy a greater period of their life free from age‐related pathology compared with wild‐type (WT) controls. In this study, we show that primary dermal fibroblasts and primary myoblasts derived from Irs1−/− mice are no more resistant to a range of oxidant and nonoxidant chemical stressors than cells derived from WT mice.